The effectiveness of Greek antitrust policy: A comparative study - Petrochilos, George A. (The Greek Review of Social Research, 1981)
The present paper explores the probable effectiveness of the Greek antimonopoly legislation in achieving its stated objective of improving the competitive forces in the Greek economy. It does so by providing a brief discussion of the relevant economic theory underlying antitrust policies, as well as an examination of the legal rules, methods and machinery required for the proper enforcement of such policies. After an outline of the key substantive points of the new Greek legislation there follows a summary discussion of the development and workings of similar policies in the US, UK and EEC and a brief critique of such policies. The paper ends with an evaluation of the prospects of the Greek legislation to be an effective tool for the promotion of competition in Greece, by reference to both the preceding discussion and factors specific to the Greek economy, and concludes that the new policy is unlikely to herald the rise of more competition in Greece. Greek businessmen need not lose their sleep on account of that policy.